Peran Surau Terhadap Perkembangan Bacaan Al Quran Anak-Anak di Nagari Lubuk Tarok Kabupaten Sijunjung (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
This study aims to analyze the role of Surau Nurul Iman in developing children's Al-Qur'an reading skills in Nagari Lubuk Tarok, Sijunjung Regency. Surau, as a traditional Minangkabau non-formal educational institution, has an important function in fostering Al-Qur'an reading skills while instilling religious values. However, modernization and the influence of technology have caused children's interest in studying at the surau to decline. This study employs a qualitative case study approach, utilizing data collection techniques such as observation, interviews, and documentation involving Quran teachers, students, parents, and community leaders. The results of the study indicate that suraus still play an important role through talaqqi learning, muraja’ah practice, and the formation of children’s religious character. Factors supporting the role of suraus include parental support, a religious social environment, and the familial relationship between teachers and students. The inhibiting factors include limited facilities, monotonous teaching methods, lack of teacher training, and the influence of gadgets on children's discipline. This study recommends the development of varied teaching methods, improving the capacity of Quran teachers, enhancing facilities and infrastructure, and collaborating with parents and the community to optimize the function of suraus.
Keywords: Surau; Quran Recitaion; Non-Formal Education; Children